Prevalence and mitigation of aflatoxins in Kenya (1960-to date) - Mutegi, C.; Cotty, P.J.; Bandyopadhyay, Ranajit (Brill, 2018)
Aflatoxins are highly toxic metabolites of several Aspergillus species widely distributed throughout the environment. These toxins have adverse effects on humans and livestock at a few micrograms per kilogram (μg/kg) concentrations. Strict regulations on the concentrations of aflatoxins allowed in food and feed exist in many nations in the developing world. Loopholes in implementing regulations result in the consumption of dangerous concentrations of aflatoxins. In Kenya, where ‘farm-to-mouth’ crops become severely contaminated, solutions to the aflatoxins problem are needed. Across the decades, aflatoxins have repeatedly caused loss of human and animal life. A prerequisite to developing viable solutions for managing aflatoxins is understanding the geographical distribution and severity of food and feed contamination, and the impact on lives. This review discusses the scope of the aflatoxins problem and management efforts by various players in Kenya. Economic drivers likely to influence the choice of aflatoxins management options include historical adverse health effects on humans and animals, cost of intervention for mitigation of aflatoxins, knowledge about aflatoxins and their impact, incentives for aflatoxins safe food and intended scope of use of interventions. It also highlights knowledge gaps that can direct future management efforts. These include: sparse documented information on human exposure; few robust tools to accurately measure economic impact in widely unstructured value chains; lack of long-term impact studies on benefits of aflatoxins mitigation; inadequate sampling mechanisms in smallholder farms and grain holding stores/containers; overlooking social learning networks in technology uptake and lack of in-depth studies on an array of aflatoxins control measures followed in households. The review proposes improved linkages between agriculture, nutrition and health sectors to address aflatoxins contamination better. Sustained public awareness at all levels, capacity building and aflatoxins related policies are necessary to support management initiatives.